Migration, Unemployment, and Over-qualification: A Specific Factors-Model Approach - Joan Muysken; Ehsan Vallizadeh; Thomas Ziesemer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper analyses the impact of the skill composition of migration flows on the host country's labour market in a specific-factors-two-sector model with heterogeneous labour (low, medium, and high skill) and price- and wage-setting behaviour. The low- and medium-skilled labour markets are characterized by frictions due to wage bargaining. Moreover, we assume bumping down of unemployed medium-skilled workers into low-skilled labour supply. Endogenous benefits create an interdependency between the two bargaining processes. Particular attention is paid to medium-skilled migration which enables us to augment the literature by replicating important stylized facts regarding medium skills, such as i) the interaction between immigration, low-skilled unemployment and medium-skilled over-qualification, ii) the polarization effect where both low- and high-skilled wages increase relative to the medium-skilled. The model is calibrated using German data. The key findings are: (i) a migration-induced supply shock of medium-skilled workers decreases the low-skilled unemployment rate because of the endogenous benefits; (ii) immigration of medium-skilled labour together with some high-skilled labour has a positive effect on output per capita; (iii) migration of only medium-skilled labour has a neutral impact on GDP per capita.
Additional information: Extra Appendices are available upon request.
Keywords: F22; J51; J52; J61; J64; 330; Medium-Skilled Migration; Wage and Price Setting; Specific Factors Model; Unemployment; Over-qualification; Wage Polarization